Identification of Factors Causing Construction Contract Breaks and Recommendations for Improvement in West Pasaman Regency - Novia, Rika; Hidayat, Benny; Suraji, Akhmad (Universitas Negeri Padang, 2024)
The implementation of construction projects in the Regional Government of West Pasaman Regency almost every year there is always a termination of the contract which results in not achieving the government's goal of increasing the standard of living of the community because the targets set by the Government are delayed and hampered. This research was carried out which aims to identify the causes of contract termination in the implementation of construction service procurement in West Pasaman Regency, analyze and evaluate the causes of contract termination in construction implementation, and determine recommendations for improvement to prevent contract termination in the implementation of construction service procurement in Pasaman Regency West. This study uses descriptive qualitative analysis based on the results of interviews with CMO and TIO for work that has terminated its contract and analyzes administrative data on termination of contracts for construction work which has experienced termination of contract. The methods used in the discussion to find out the factors that cause construction contract termination are the Fault Tree Analysis (FTA) Method and the Obtain Cut Set (MOCUS) Method. From this study it can be concluded that the main factor causing the breakup of construction contracts is the owner's firmness with the performance of the provider, the provider being evaluated is unable to carry out the work, the contract termination should be carried out earlier, not waiting for the end of the year and not providing an extension of the implementation period past the fiscal year and the owner is negligent. in controlling the contract. While the supporting factors that cause the termination of the contract are the provider's fault, namely poor project management, the practice of borrowing company flags, not having capital, not heeding the instructions of the owner and field supervisor as well as other factors, namely disturbance factors from the community around the work location, weather, selection of providers and material supply. For recommendations for future improvements, it is recommended that the owner carry out control of the construction contract more optimally and the provider is more professional at work. This study analyzes the factors that cause construction contract terminations only from the owner's point of view, therefore further research is still needed from the point of view of job providers and supervisors to see the characteristics and possibilities of other different factors.